THE NEED FOR UNDERSTANDING PEKALONGAN LOCAL CULTURE FOR BIPA LEARNERS AS A MEDIUM FOR ENVIRONMENTAL ADAPTATION - Diah Puspitaningrum, M.Pd.; Antika Bela Laelatun Hana (2025)
BIPA learning provided to foreign students is carried out to provide knowledge and language proficiency. Not only language proficiency but also fulfilling cultural understanding as a means of survival. This study aims to explain the needs of foreign students to understand the local culture of Pekalongan as a region with rich local cultural wisdom. This descriptive qualitative research method analyzes based on questionnaire and interview data collection techniques with data sources of seven foreign students from Thailand, Malaysia, and the Philippines. The questionnaire is elaborated with questions about the experience of learning Indonesian and opinions on local Pekalongan culture. BIPA students who have no previous experience learning Indonesian (85%) need an understanding of Pekalongan culture integrated into learning through teaching materials and learning media. Problems that arise as obstacles in carrying out academic activities show a figure of 71.4%. One of the difficulties in adapting to local culture is food and traditions that are not familiar and the meaning of each tradition is not understood. This proves the importance of BIPA learning by incorporating local Pekalongan cultural content to provide insight as an effort to adapt to the environment.